RELEVANSI INSTRUMEN ASESMEN PEMBELAJARAN PAI TERHADAP BUDAYA KEPESANTRENAN PESERTA DIDIK DI MADRASAH ALIYAH - Rachmawati, Nuzulia; Chumairoh, Lutfi; Purwoko, Purwoko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT This study aims to analyze the relevance of Islamic Religious Education (PAI) learning assessment instruments to the Islamic boarding school culture of students at MA Darul Hikmah Kyai Abdan. Pesantren culture, as a characteristic of Islamic boarding school-based educational institutions, contains strong religious, moral, and disciplinary values. These values should ideally be reflected in PAI assessment instruments, so that the assessment measures not only cognitive aspects, but also religious behavior, attitudes, and skills. This study used a qualitative approach with a case study method. Data were collected through direct observation in the madrasah environment, in-depth interviews with Islamic boarding school teachers, and document analysis of the assessment instruments used. The results showed that most of the assessment instruments applied still focused on cognitive aspects, while the measurement of Islamic boarding school values such as etiquette, exemplary behavior, and daily worship practices had not been optimally accommodated. This finding indicates the need to develop assessment instruments that are integrative, contextual, and holistic. These instruments are expected to be able to measure all of students' religious competencies, including the affective and psychomotor dimensions, in accordance with the character and culture of the Islamic boarding school. The implications of this research encourage the formulation of authentic assessments that are relevant to the characteristics of students, local contexts, and Islamic boarding school values, so that the evaluation process can be fairer, more comprehensive, and reflect the goals of Islamic Education in Islamic boarding school environments. ABSTRAK Penelitian ini bertujuan menganalisis relevansi instrumen asesmen pembelajaran Pendidikan Agama Islam (PAI) dengan budaya kepesantrenan peserta didik di MA Darul Hikmah Kyai Abdan. Budaya kepesantrenan, sebagai ciri khas lembaga pendidikan berbasis pesantren, mengandung nilai-nilai keagamaan, moral, serta kedisiplinan yang kuat. Nilai-nilai tersebut idealnya tercermin dalam instrumen asesmen PAI, sehingga penilaian tidak hanya mengukur aspek kognitif, tetapi juga perilaku, sikap, dan keterampilan keagamaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi langsung di lingkungan madrasah, wawancara mendalam dengan guru PAI, serta analisis dokumen instrumen asesmen yang digunakan. Hasil penelitian menunjukkan bahwa sebagian besar instrumen asesmen yang diterapkan masih berfokus pada aspek kognitif, sementara pengukuran nilai-nilai kepesantrenan seperti adab, keteladanan, serta praktik ibadah harian belum terakomodasi secara optimal. Temuan ini mengindikasikan perlunya pengembangan instrumen asesmen yang bersifat integratif, kontekstual, dan holistik. Instrumen tersebut diharapkan mampu mengukur seluruh kompetensi keagamaan peserta didik, termasuk dimensi afektif dan psikomotor, sesuai dengan karakter dan budaya pesantren. Implikasi penelitian ini mendorong perumusan asesmen autentik yang relevan dengan karakteristik peserta didik, konteks lokal, dan nilai-nilai pesantren, sehingga proses evaluasi dapat lebih adil, menyeluruh, dan mencerminkan tujuan pendidikan PAI di lingkungan kepesantrenan.